ANALYSIS OF AIRY POINT APPLICATION ON LINE SCALE CALIBRATION IN RCM LIPI - Nadya Larasati Kartika; Nurul Alfiyati (Badan Standardisasi Nasional, 2018)
Calibration of line scale in the Research Center for Metrology LIPI Indonesia (RCM-LIPI) is traceable to one dimensional measuring machine (SIP machine). Capability of the SIP machine table used as the base of line scale, however, covers only up to 400 mm and can be extended to 1000 mm using shifting methods. Supporting point as a method to maintain line scale still straight during measurement should be applied on machine table. For line scale ranged 400 mm, supporting point can be attached because the whole artefact is on the table, while some of the industrial instruments have scales above 400 mm, this mean slightly difficult to attach supporting point. This paper described an appropriate supporting points setting and their influence in line scale calibration ranged 500 mm by designed two systems supporting point attachment, they are L = 500 mm and L = 350 mm. As for the supporting points, airy points were used, because they were the most suitable for line scales with the pattern at the top plane. Each design is analysed using error graph and En score to determine the most suitable design for 500 mm line scale calibration.